Strategi daya tindak wanita yang hidup dengan hiv dalam melaksanakan kefungsian sosial mereka di Bandung, Indonesia - Sutiaputri, Lina Favourita (2016)
Woman living with HIV are confronted with all types of barriers that lead to stress in life. Social pressures and stresses faced have encouraged women living with HIV to undertake relevant coping strategies in order to achieve their full social functioning. This qualitative study focusing on case study, involved five (5) informants of women living with HIV. The study also included eight (8) volunteers from the Warga Peduli AIDS (WPA) amd three (3) family members, which were all selected through purposive sampling. Data collection was conducted through indepth interviews, focus group discussions, participation observation, and documentation study, which was done in two (2) years in Kelurahan Kebon Pisang, Kecamatan Sumur Bandung, Kota Bandung, Indonesia. Findings have indicated that women living with HIV do face complex pychological and social problems, which include contraction of HIV from husbands who were injecting drug users; economic problem due to high medical expenses; disclosure problems due to negative stigma that limits the needed social support system